An Evaluation of Mandarin Learning Apps Designed for English Speaking Pre-schoolers - Neumann M; Wang Y; Qi GY; Neumann D (Association for the Advancement of Computing in Education (AACE), 2019)
Touch screen tablets such as iPads are becoming increasingly popular as educational tools to support children’s first language learning in pre-schools. Apps can also be used to support early learning of a second language in English-speaking countries. However, little work has been done to evaluate these apps. The present research developed criteria for assessing Mandarin learning apps and applied them to evaluate 28 Mandarin apps for English-speaking pre-schoolers. The criteria included the domains of interactivity, usability, cultural awareness, collaboration, language and literacy content, and learning outcomes. The application of the criteria showed that half the Mandarin learning apps lacked key educational features essential for second language learning. The categories in which the apps scored most highly were interactivity, cultural awareness, usability, and language and literacy content. The apps scored lowest in the categories of collaboration and provision of learning outcomes. The findings suggest that further research is needed to inform best practice, app design, and to provide guidelines that help teachers select quality apps to support second language learning.
(c) Copyright Owner Publishers - Accepted version permitted on institutional repository.
Keywords: apps; Chinese; evaluation; iPads; Mandarin; pre-schoolers; second language learners; Touch screen tablets; 1303 Specialist Studies in Education